(untitled) (Doctor Virtualis, 2023)
This paper investigates the definition of “justice” and its transformation, from Aquinas (analogical) to Cajetan (univocal). Through the commentaries of Cajetan to the S. Th., this contribution also deeps into the connection between Logic and Moral Philosophy. We intend to deepen the relationship between justice and the common good using the analogy (Aquinas) or not (Cajetan). This work also refers to the thesis of S. Hofstadter according to which the analogy is almost a cognitive a priori with which man conceptualizes the world and progresses in knowledge, bearing in mind the role that analogy played in Cajetan’s thought. If the analogical notion of justice renders much better the teaching of Aquinas, it is observed that Cajetan interpretates the same virtue according to univocity, because of his previous conception of the analogy. Therefore, we have two notions of “justice” related to the common good and the rest of the moral virtues. How could this affect the Ethics and the political reflections? What is the relationship between the suprema potestas, the government, etc.? Again, we have now two different ways of arguing and representing the world and its relations.